GENEROSITY OF PHILEAS FOGG IN JULES VERNE’S AROUND THE WORLD IN 80 DAYS - Norlin Pagama; Sarah Kamagi; Ceisy Wuntu (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this study aimed to reveal the generosity in Jules Verne’s Around the World in 80 Days. The research is categorized as qualitative research since the data were in the form of words and all data in this research gathered from library book and internet. There are two main sources here. In this case, the primary source is from Jules Verne’s Around the World in 80 Days. The secondary sources are all references that support the analysis that could support this research. The result of this research shows that the generosity of the main character Phileas Fogg. Fogg is a truly gentleman. Being victorious leads people to be more known, gained reputation and respect, also money, but those things are not his priority because he already have enough. Phileas Fogg dare to around the world in 80 days. In his journey, he met Aouda who fell in love with Phileas Fogg because of his generosity, not by his money. Then, Phileas Fogg won his bet to around the world in 80 days and married Aouda.